A Brief Review on Radiant Cooling Panel with Different Chilled Water Pipe Configurations - Radzai M.H.M.; Lim C.W.; Yaw C.T.; Koh S.P.; Ahmad N.A.; Shakeri M.; Pasupuleti J. (Penerbit Akademia Baru, 2023)
Radiant cooling systems are commonly applied in commercial applications because of their energy-saving potential. This potential can be further enhanced by evaluating the cooling performance of the radiant cooling panel in terms of flow configurations. Although studies have been conducted on the flow configurations of the radiant cooling panel, the most suitable flow configurations have yet to be determined. The conventional serpentine flow configuration does not bring out the best cooling performance of the radiant cooling panel, therefore different flow configurations are still needed to be explored. This study conducted a quick literature review on the different radiant cooling systems as well as radiant cooling panel with different chilled water pipe configurations. The objective of this review is to provide a brief comparison of the performance of radiant cooling panel with different chilled water pipe configurations and to suggest further studies for the system development. The cooling characteristics and heat transfer of the panel are investigated by using numerical study. A comparison between the designs of flow configurations is presented. In all of the cases, the plate area and flow volume are fixed. Based on the findings obtained, applying a different chilled water pipe configuration on the radiant cooling panel will affect the flow uniformity and also the temperature distribution uniformity. An optimized flow configurations for the radiant cooling panel is important for enhancing the overall efficiency of the system 2022,Journal of Advanced Research in Fluid Mechanics and Thermal Sciences.All Rights Reserved